Antibiotic susceptibility and biofilm pattern in Staphylococcus aureus from clinical sources in Diyala Governorate - Esam H. Hummadi; Zahraa Laith Ramadan (ASJ - Academic Science Journal, 2026)
Staphylococcus aureus is a pathogenic bacteria that causes a variety of diseases, from skin infections to serious and fatal infections, due to producing a variety of virulence factors. Biofilm is the most important virulence factors that confers S. aureus the severity. This study aims to isolate S. aureus from different sites of the human body and investigate the distribution of antibiotic resistance and biofilm profiles and the relationship between them. In this study, 250 clinical specimens were collected from teaching laboratories in Baqubah Teaching Hospital, Diyala Province, Iraq, from which, fifty isolates were selected to conduct this study. Based on morphological and biochemical tests, the isolates were identified, and the VITEK2 system confirmed the identities of the isolates. The isolates were tested with 12 antibiotics belong to different groups. The isolates showed high resistance to Oxacillin (100%), azithromycin (68%). In contrast, a high susceptibility percentage was observed with nitrofurantoin (84%), chloramphenicol (90%), rifampin (76%), gentamicin (68%), clindamycin (70%), tetracycline (48%), norfloxacin (62%), trimethoprim-sulfamethoxazole (60%), levofloxacin (62%), and ciprofloxacin (60%). The biofilm formation test revealed that 22(44%) of S. aureus isolates were strong biofilm-forming, 26(52%) were moderate, and 2(4%) were weak biofilm-forming. This study revealed a correlation between the isolates with strong biofilm and their antibiotic resistance pattern. In conclusion, these recent results may provide a basis to treat S. aureus by developing new antibiotics.